1979
DOI: 10.1093/infdis/140.6.952
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Species of Candida, Cryptococcus, and Torulopsis by Gas-Liquid Chromatography

Abstract: Gas-liquid chromatography was used to identify species of Candida, Cryptococcus, and Torulopsis by fatty-acid analysis of the whole-cell hydrolysate. Candida albicans characteristically revealed 2-OH C14:0 and C19:0 (chain length:number of double bonds); these were absent in other organisms. Candida curvata was characterized by a ratio of C16:1 to C16:0 of greater than 1.0. Candida guilliermondii contained C10:0, and Candida tropicalis had no C12:0, these features were used for their identification. Cryptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Arachidonic acid was detected among the very long chain fatty acids (C [19][20][21][22][23][24][25] ) of the yeast Rhodotorula (19). The occurrence of arachidonic acid in C. neoformans and C. albicans has not been verified (6,15). It is possible that the growth conditions and/or methods of fatty acid extraction and identification were not optimized for detecting very long chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid was detected among the very long chain fatty acids (C [19][20][21][22][23][24][25] ) of the yeast Rhodotorula (19). The occurrence of arachidonic acid in C. neoformans and C. albicans has not been verified (6,15). It is possible that the growth conditions and/or methods of fatty acid extraction and identification were not optimized for detecting very long chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Several chemotaxonomic studies, which include the examination of the total cell fatty acid content, have also been done. In bacterial and yeast taxonomy, the determination of fatty acids has proved to be a most useful tool (Moss & Dees, 1976;Gunasekaran & Hughes, 1980;Cottrell et al, 1985;Kock et al, 1985a, b). Abel et al (1963) demonstrated, that micro-organisms could be classified into genera and species on the basis of their chemical composition determined by gas chromatography, while Rattray et al (1975) and Shaw (1974) discussed the use of cellular fatty acid composition for the identification of various yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…Abel et al (1963) demonstrated, that micro-organisms could be classified into genera and species on the basis of their chemical composition determined by gas chromatography, while Rattray et al (1975) and Shaw (1974) discussed the use of cellular fatty acid composition for the identification of various yeasts. This technique was subsequently used by various workers to identify bacteria and yeasts (Kaneko, 1976;Gangopadhyay et al, 1979;Moss et al, 1982). Unfortunately these studies differed in the cultivation procedures used, which, according to the literature, significantly influence cellular fatty acid composition (Deinema, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have since followed. In 1979, Gangopadhyay et al 8 used cellular long-chain FAs to differentiate between 38 isolates of anamorphic genera of Candida, Cryptococcus and Torulopsis. In 1980, Gunasekaran and Hughes 9 used FA profiles to characterise 85 strains of Candida based on the presence or the absence of certain FAs.…”
mentioning
confidence: 99%